(untitled) (Journal of Hama University, 2021)
The idea of "We-Qoup" which appeared in the poems of the conquests poets affectid the fighters themselves and made them fight to defend Islam and the muslims and not for pride and egoism as it was in the pagan period befor islam . This research high lights the idea working for the group and not for oneself according to the Islamic education in the first period Islam .